Generálna klauzula bezdôvodného obohatenia v českom práve včera a dnes: najväčšie zmeny v občianskom zákonníku - Veronika Zoričáková (Acta Universitatis Carolinae. Iuridica)
In the presented article, the author deals with the development of the general clause of unjustified enrichment in Czech conditions, with an emphasis on the insufficiencies of the general clause in the Civil Code 64, which caused long-term problems in legal practice and, in a way, were the catalyst for a significant material change, which was translated into the current wording of the general clause in § 2991 of the Civil Code. What preceded the current setting of the general clause and specific types of unjustified enrichment in § 2991 of the Civil Code and what theoretical, but mainly practical benefit those individual changes to the current Czech legislation have, is the subject of the presented analysis.